THE IMPACT OF DYNAMIC CAPABILITIES AND STAKEHOLDER PRESSURE ON SUSTAINABLE SUPPLY CHAIN PERFORMANCE IN THE MANUFACTURING INDUSTRY - Mohammad Syahrizal Sukmaya; Wahyuningsih Santosa; Triwulandari Satitidjati Dewayana (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study aims to analyze how dynamic capabilities and stakeholder pressure influence sustainable supply chain performance, with green supply chain innovation (GSCI) serving as a mediating variable in Indonesian manufacturing companies. Dynamic capabilities are represented by digital leadership, environmental awareness, and organizational learning, while stakeholder pressure is positioned as the main external factor. The research uses a quantitative approach with partial least squares–structural equation modeling (PLS-SEM) on data collected from 152 respondents. The results show that digital leadership, environmental awareness, and stakeholder pressure positively influence GSCI, while organizational learning has no significant effect. Furthermore, GSCI is proven to positively affect sustainable supply chain performance and mediates the influence of digital leadership, environmental awareness, and stakeholder pressure on sustainable supply chain performance, but does not mediate the relationship between organizational learning and sustainable supply chain performance. These findings confirm that green supply chain innovation is a key mechanism in translating internal capabilities and external pressures into improved sustainable supply chain performance, contributing theoretically to the development of Dynamic Capabilities Theory and Stakeholder Theory, as well as providing practical implications for sustainable supply chain management in the manufacturing sector.